Sodium/Hydrogen Exchanger 1 Participates in Early Brain Injury after Subarachnoid Hemorrhage both in vivo and in vitro via Promoting Neuronal Apoptosis. Issue 8 (August 2019) - Song, Huangcheng; Yuan, Shuai; Zhang, Zhuwei; Zhang, Juyi; Zhang, Peng; Cao, Jie; Li, Haiying; Li, Xiang; Shen, Haitao; Wang, Zhong; Chen, Gang
Sodium/hydrogen exchanger 1 (NHE1) plays an essential role in maintaining intracellular pH (pHi) homeostasis in the central nervous system (CNS) under physiological conditions, and it is also associated with neuronal death and intracellular Na + and Ca 2+ overload induced by cerebral ischemia. However, its roles and underlying mechanisms in early brain injury (EBI) induced by subarachnoid hemorrhage (SAH) have not been fully explored. In this research, a SAH model in adult male rat was established through injecting autologous arterial blood into prechiasmatic cistern. Meanwhile, primary cultured cortical neurons of rat treated with 5 μM oxygen hemoglobin (OxyHb) for 24 h were applied to mimic SAH in vitro . We find that the protein levels of NHE1 are significantly increased in brain tissues of rats after SAH. Downregulation of NHE1 by HOE642 (a specific chemical inhibitor of NHE1) and genetic-knockdown can effectively alleviate behavioral and cognitive dysfunction, brain edema, blood-brain barrier (BBB) injury, inflammatory reactions, oxidative stress, neurondegeneration, and neuronal apoptosis, all of which are involved in EBI following SAH. However, upregulation of NHE1 by genetic-overexpression can produce opposite effects. Additionally, inhibiting NHE1 significantly attenuates OxyHb-induced neuronal apoptosis in vitro and reduces interaction of NHE1 and CHP1 both in vivo and in vitro . Collectively, we can conclude that NHE1 participates in EBI induced by SAH through mediating inflammation, oxidative stress, behavioral and cognitive dysfunction, BBB injury, brain edema, and promoting neuronal degeneration and apoptosis.